(untitled) (Bangladesh Journal of Botany, 2022)
Purple blotch caused by Alternaria porri is one of the most destructive diseases of onion which inflicting considerable bulb yield loss. To find the suitable biointensive management option, efficacy of different essential oils and bio-agents was evaluated. Effects of various treatments were assessed in terms of quality attribute of plant and disease magnitude. The combined application of essential oil and Trichoderma viride was found to be supportive to increase the plant height, neck thickness and foliage in two varieties e.g., Agrifound Light Red and NHRDF Red-3. The mean incidence of purple blotch (40.7 and 38.9%) was observed in both the varieties in response of combined application Neem oil and T. viride. In result of lowest disease pressure, the highest yield 343.86 and 304.08Q/ha was found in NHRDF Red-3 and Agrifound Light Red, respectively. In study of temporal dynamics of blotch severity, an exponential increase in severity was found between 60 to 90-DAT. The information generated in the present study may be helpful to develop a biointensive management module which will facilitate the onion production. Bangladesh J. Bot. 51(3): 541-546, 2022 (September)